Analysis of the Impact of Batang Arau River Pollution on Communities and the Environment Around the River - Rahayu, Lisa; Eni Kamal; Aldri Frinaldi; Rembrandt; Abdul Razak; Widya Prarikeslan (Jurnal Kesehatan Cendikia Jenius, 2024)
Rivers play an important role in supporting people's lives. However, poor river water quality due to pollution has a significant impact on the survival of coastal communities and the condition of the surrounding environment. To overcome water pollution, it is important to implement stricter regulations that are regulated in Law no. 32 of 2009 supplemented by Republic of Indonesia Government Regulation Number 22 of 2021. The research carried out was quantitative descriptive in nature, highlighting the impact on the water quality of the Batang Arau river from examining BOD, COD and TSS, which are river water pollution parameters. The research results show that in 2023, the results of examining COD parameters in the upstream river area will exceed the set quality standard limit, namely 25 mg/L. The recorded value reached 87.3 mg/L, which indicates the presence of very high levels of organic chemicals in these waters. In 2024, inspection results show significant improvements in the water quality of the Batang Arau River. It was concluded that the water quality of the Batang Arau river shows a positive trend. The pollution conditions that occurred in 2023, especially in the COD and BOD parameters in the upstream river, have been successfully improved by 2024. This shows the success of efforts to improve environmental quality carried out in the river area.